Long-term impact of national tuberculosis program interventions on incidence and disparities by age and geography - Chien, Yuan-Shan; Lin, Ting-Yu; Lai, Chao-Chih; Hsu, Chen-Yang; Hsieh, Yu-Chu; Lin, Shin-Yi; Wang, Hsiao Chi; Chen, Hung-Pin; Chen, Hsiu-Hsi; Luh, Dih-Ling; Yeh, Yen-Po (BMC infectious diseases, 2025)
Background Evaluations of the national tuberculosis control programs (NTPs) frequently lacked insights into the uneven long-term impacts on distinct age groups and geographic regions. Methods We analyzed tuberculosis cases notified from 1990 to 2019 in Changhua, Taiwan. A Bayesian hierarchical change-point model was developed to estimate the NTP’s effects on different age groups and townships and project the long-term tuberculosis incidence trend to 2035. Results A total of 23,149 tuberculosis cases were identified. Tuberculosis incidence peaked at 106.6 per 100,000 in 2002, then declined steadily. Annual reductions estimated after the establishment of the laboratory network, directly observed therapy implementation, and post-2015 projections were 3.3%, 4.5%, and 5.7%, respectively. Tuberculosis incidence fell by 44.8% from its peak to 2016, with our model projecting a further reduction of 69.0% by 2035. The predicted overall incidence (per 100,000) is 15.7 in 2035, with age-specific rates and corresponding projected reductions expected to be 1.6 (68.1%), 3.6 (75.1%), 12.3 (76.6%), and 113.1 (65.4%) for ages 0 to 29, 30 to 49, 50 to 69, and over 70 years old, respectively. Older adults constituted over two-thirds of cases, showing intractable reduction. Geographical disparities persisted, with higher incidences noted in remote rural townships. Conclusions The NTP has significantly decreased tuberculosis incidence in Changhua; however, additional efforts will likely be required to reach the END TB targets by 2035. Future programs must expand preventive treatments for latent tuberculosis infection and consistently address barriers within the TB care cascade, with a specific focus on the elderly and residents of underserved areas.